Cat scratch disease and lymph node tuberculosis in a colon patient with cancer. (12th December 2013) - Matias, M; Marques, T; Ferreira, M A; Ribeiro, L
Abstract : A 71-year-old man operated for a sigmoid tumour remained in the surveillance after adjuvant chemotherapy. After 3 years, a left axillary lymph node was visible on CT scan. The biopsy revealed a necrotising and abscessed granulomatous lymphadenitis, suggestive of cat scratch disease. The patient confirmed having been scratched by a cat and the serology for Bartonella henselae was IgM+/IgG−. Direct and culture examinations for tuberculosis were negative. The patient was treated for cat scratch disease. One year later, the CT scan showed increased left axillary lymph nodes and a left pleural effusion. Direct and cultural examinations to exclude tuberculosis were again negative. Interferon-γ release assay testing for tuberculosis was undetermined and then positive. Lymph node and pleural tuberculosis were diagnosed and treated with a good radiological response. This article has provides evidence of the importance of continued search for the right diagnosis and that two diagnoses can happen in the same patient.